The Formation of Small Market Places in a Competitive Economic Process–The Dynamics of Agglomeration - Baesemann, Robert C. (Econometrica, 1977)
In analyzing the city as an economic institution, it seems reasonable to ask if the advantages of proximity are sufficient to assure that traders will form and maintain a market place. This process is called agglomeration. A general theorem concerning iterative spatial games is developed first. A spatial general equilibrium model comprised of a sequence of pure trade economies is proffered. Restrictions on transport technologies sufficient to assure agglomeration are determined. The possibility of a policy maker speeding the process of agglomeration is demonstrated. In conclusion, the optimality properties of the model are discussed. The research draws heavily on the works of A. Weber [8] and G. Debreu [2]. The model includes a dynamic adjustment process which is developed from individuals' maximizing behavior.